Unpacking digital transformation – Constructing a framework based on industry use cases - Khawaja Asjad Saeed; Andrew William Green; Alison Brooke Hedrick (Journal of Innovation & Knowledge, 2025)
Based on industry use cases, we identify six distinct types of digital transformation (DT), each grounded in a specific concept or enabling technology. These DT types can be implemented individually or combined to drive transformation initiatives. While deploying a single DT type often focuses on improving operational efficiency or streamlining existing workflows, initiatives that combine multiple DT types tend to pursue more ambitious goals, such as the creation of new products, services, or business models. However, the complexity increases significantly with the integration of multiple DT types, as organizations must not only address behavioral changes but also overcome technical challenges involving systems integration, data architecture, and interoperability.